Mindfulness-Based Intervention for Chinese Breast Cancer Patients: A Systematic Review and Meta-Analysis. (October 2021) - Zhang, Anao; Jing, Shijie; Solomon, Phyllis; Brose, Anna
Purpose: To systematically review and meta-analyze all published studies, written in Chinese and published in China, focusing on mindfulness-based interventions for Chinese breast cancer patients' mental health and quality of life outcomes. Methods: Following the Cochrane guideline, this study searched across five electronic debases, two professional websites, two major Chinese oncology journals, and reference lists of existing reviews and included studies. Meta-analysis was conducted using meta-regression with robust variance estimation. Publication bias and risk of bias were assessed and evaluated in the final analysis. Results: A final of 35 clinical trials included 126 effect sizes and 3, 100 participants. Studies reported an overall large and statistically significant treatment effect, g = 0.963, p < .001. Conclusions: Mindfulness-based interventions were significantly effective for Chinese breast cancer patients and are recommended for oncology social workers. Moderator analyses identified group-based mindfulness interventions as significantly more effective than individual-based interventions, and mindfulness-based interventions delivered as therapeutictreatment were significantly more effective than ones delivered as supportive treatment.